Trends and Correlates of Breakthrough Infections With SARS-CoV-2 - Yamal, Jose-Miguel; Appana, Savitri; Wang, Mengxi; Leon-Novelo, Luis; Bakota, Eric; Ye, Yuanqing; Sharma, Shreela; Morrison, Alanna C.; Marko, Dritana; Linder, Stephen H.; Rector, Alison; Jetelina, Katelyn K.; et al. (Frontiers in Public Health, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) delta variant has been hypothesized to decrease the efficacy of COVID-19 vaccines. Factors associated with infections with SARS-CoV-2 after vaccination are unknown. In this observational cohort study, we examined two groups in Harris County, Texas: (1) individuals with positive Nucleic Acid Amplification test between 12/14/2020–9/30/2021 and (2) the subset of individuals fully vaccinated in the same time period. Infected individuals were classified as a breakthrough if their infection occurred 14 days after their vaccination had been completed. Among fully vaccinated individuals, demographic and vaccine factors associated with breakthrough infections were assessed. Of 146,731 positive SARS-CoV-2 tests, 7.5% were breakthrough infections. Correlates of breakthrough infection included young adult age, female, White race, and receiving the Janssen vaccine, after adjustments including the amount of community spread at the time of infection. Vaccines remained effective in decreasing the probability of testing positive for SARS-CoV2. The data indicate that increased vaccine booster uptake would help decrease new infections.